2023
DOI: 10.1177/0013161x231159092
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring Teachers’ Instructional Practice Profiles: Do Distributed Leadership and Teacher Collaboration Make a Difference?

Abstract: Purpose: While the literature includes multiple studies on the relationship between school leadership and instructional quality, they often use instructional practice as a continuous variable, assuming that a teacher would perform all sub-dimensions of instructional practice at a similar rate and failing to link distributed leadership to classroom teaching. Addressing these gaps in the literature, this study aims to identify teacher- and school-level latent profiles of teachers’ instructional practices and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…There are also several recent studies that focus on teacher competence profiles (Bae et al, 2020;Jang, Yoo, & Rubadeau, 2023;Özdemir, Kılınç, Polatcan, Turan, & Bellibaş, 2023). Almost all studies, including this paper, identified teachers who struggle with classroom instruction and teachers who are proficient.…”
Section: Comparison Of the Findings With Other Studiesmentioning
confidence: 99%
“…There are also several recent studies that focus on teacher competence profiles (Bae et al, 2020;Jang, Yoo, & Rubadeau, 2023;Özdemir, Kılınç, Polatcan, Turan, & Bellibaş, 2023). Almost all studies, including this paper, identified teachers who struggle with classroom instruction and teachers who are proficient.…”
Section: Comparison Of the Findings With Other Studiesmentioning
confidence: 99%
“…The concept of teaching collaboration revolves around the voluntary engagement of two or more parties who actively participate as equal partners, collectively assuming responsibility for both positive and negative outcomes (Khasawneh et al, 2023;Özdemir et al, 2023). Both parties involved in the collaborative effort acknowledge and strive towards a shared objective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research is based on the hypotheses that a work environment dominated by team innovativeness and that the power of a collaborative culture can trigger more willingness in the teachers to improve their instructional practices (Bellibaş, 2023;Buyukoze et al, 2022;Özdemir, 2020;Özdemir et al, 2023). We investigated the relationship among team innovativeness and to what extent an innovative climate impacts teachers' instructional and professional practices, the key outcomes, including sub-contextual effects, such as exchange, coordination, and professional practices, basing our research on the teachers' perceptions.…”
Section: Introductionmentioning
confidence: 99%